University-industry partnerships : fostering strategic lingkages at institutions of higher learning in Malaysia - Siti Hamisah Tapsir, 1961- 209974; Nor Aieni Mokhtar 279100; Ahmad Fauzi Ismail, Prof. Datuk Ts. Dr., 1966- 592229; Abdul Karim Mirasa, 1953- 225367; Suhaila Mohd. Sanip 318921; Fazilah Abd. Manan 294946 (Skudai, Johor : Penerbit UTM Press, 2010)
Includes bibliographical references and index